2022
DOI: 10.1002/viw.20220029
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic therapy in cancer treatment: Progress and outlook

Abstract: Cancer is one of the major diseases that endanger human health. Current treatment options have low patient tolerance, poor prognosis, and strong side effects. Pulsed electromagnetic therapy can selectively kill cancer cells by taking advantage of their own electromagnetic sensitivity specificity. Pulsed electric fields (PEFs), pulsed electromagnetic fields (PEMFs), and cold atmospheric plasma (CAP) are three main means that have promising application in cancer therapy.Pulsed electromagnetic therapy showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…[46,47] Many studies also report other cell death modalities following IR, such as necroptosis, ferroptosis, and pyroptosis which have a distinct outcome on the immune system. [48][49][50][51] Earlier studies have shown that when cells under the oxidative stress, treatment with Z-VAD-FMK, necropstatin-1, and ferrostatin-1 could respectively prevent activation of regulators (e.g., caspase, TNFalpha, and ferroptosis), which are able to inhibit cell death in a degree. [52][53][54] Interestingly, in our studies, regulators activation under 223 Ra seem to be optional for cell death to occur, as cells continue to die by other cellular stress mechanisms and cell death modalities.…”
Section: Discussionmentioning
confidence: 99%
“…[46,47] Many studies also report other cell death modalities following IR, such as necroptosis, ferroptosis, and pyroptosis which have a distinct outcome on the immune system. [48][49][50][51] Earlier studies have shown that when cells under the oxidative stress, treatment with Z-VAD-FMK, necropstatin-1, and ferrostatin-1 could respectively prevent activation of regulators (e.g., caspase, TNFalpha, and ferroptosis), which are able to inhibit cell death in a degree. [52][53][54] Interestingly, in our studies, regulators activation under 223 Ra seem to be optional for cell death to occur, as cells continue to die by other cellular stress mechanisms and cell death modalities.…”
Section: Discussionmentioning
confidence: 99%
“…In localized surface plasmon resonance (LSPR) nanomaterials, charge transfer upon light excitation can occur instantaneously, endowing nanoscale SERS sensors with ultrafast response capabilities that are particularly suitable for the precise real-time monitoring of biological molecular changes. 139 Moreover, Raman scattering spectra resulting from molecular vibrations and rotations are highly specific. Raman spectroscopy can provide fingerprint-like detection information for multi-target, multi-state biological molecules, offering significant advantages in personalized medicine based on fluid diagnostics.…”
Section: Nanoscale Reviewmentioning
confidence: 99%
“…This suggests that NEDD8 may be used as a potential target for the treatment of lung cancer. At the same time, this targeted therapy may also be used as an adjunct to radiotherapy (77), chemotherapy (83) and pulsed electromagnetic therapy (84).…”
Section: Lung Cancer Treatment Targeting Neddylationmentioning
confidence: 99%